Violência doméstica e educação: o olhar da escola sobre esta realidade - Bezerra, Patricia dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This coursework is about domestic violence in the context of Childhood Education. Its goal is to analyze and to understand how teachers and schools take a stand before the domestic violence that is present in Childhood Education, through theoretical study, in a sample of periodicals of the area. Specifically, it seeks (1) to analyze the perception of the professionals of education about domestic violence from researches carried out in the area; (2) to identify in the papers found, actions that the schools have taken with its professionals about the domestic violence; (3) to understand the relation of the teachers and their students, when they suffer domestic violence and; (4) to investigate how the relation of school and family takes place when the issue of violence is addressed. It was opted for the qualitative approach research, bibliographical review, with the study of published researches of the last ten years, found in databases, such as Scientific Electronic Library Online (SciELO) and in the Portal de Periódicos da CAPES/MEC. Among the results obtained in this study, we related the bigger quantity of scientific production focused on the heath area and in relation to the educational area, few results were found. We identified that the school is not enough prepared to deal with the domestic violence in the school context, scaring the ones inserted in it. Therefore, these presented factors, led to the idea that the current subject is very little studied at schools and with professionals of the area

Este trabalho trata da temática da violência doméstica no âmbito da Educação infantil. Tem como objetivo analisar e compreender como professores e escola se posicionam diante da violência doméstica que se apresenta na Educação Infantil, através do estudo teórico, em uma amostra de periódicos da área. Especificamente se busca (1) analisar a percepção dos profissionais de educação sobre violência doméstica a partir de pesquisas já realizadas nessa área; (2) identificar nos trabalhos encontrados, ações que as escolas tenham tomado com seus profissionais referentes à violência doméstica; (3) compreender a relação do professor e do seu aluno, quando ele sofre violência doméstica e; (4) investigar como se dá a relação da escola e família quando abordada a questão da violência. Optou-se pela pesquisa de abordagem qualitativa, de revisão bibliográfica, com o estudo de pesquisas publicadas nos últimos dez anos, encontrados em bancos de dados como Scientific Electronic Library Online (SciELO) e no Portal de Periódicos da CAPES/MEC. Dentre os resultados obtidos neste estudo, relacionamos a maior quantidade de produção científica voltada para à área da saúde e em relação a área da educação, encontrou-se poucos resultados. Identificamos que a escola ainda não possui preparo suficiente para lidar com a violência doméstica no contexto escolar, amedrontando aqueles que nela estão inseridos. Portanto, estes fatores apresentados, nos levaram a pensar que o presente tema é pouco estudado nas escolas e com os profissionais da área
Keywords: Violência familiar; Educação; Escolas; Educação de crianças; Professores